MAPPING ISLAMIC CONTENT IN MEDICAL & HEALTH SCIENCE EDUCATION CURRICULUM AT THE FACULTY OF MEDICINE AND HEALTH SCIENCES MUHAMMADIYAH UNIVERSITY MAKASSAR (International Conference on Social and Islamic Studies, 2022)
Medical and Health Sciences based on natural sciences, especially empirical biomedical sciences; often difficult to integrate with Islamic knowledge based on metaphysics and religious morality. The curriculum and science of Medicine and Health adopted from the secular western world does not make religious content a part of the curriculum for Medical and Health Education.The Faculty of Medicine and Health Sciences (FKIK) Muhammadiyah University (Unismuh) Makassar as the provider of medical education and health sciences has a mandate to include Islamic content in the curriculum of medical education and health sciences that they manage.This paper maps out Islamic content in the medical and health education curriculum at Unismuh Makassar using a normative study approach.Islamic teaching materials in the medical and health education curriculum at FKIK Unismuh Makassar can be mapped into three types, namely: (1) generic-Islamic topics; (2) Islamic professional ethics; (3) integrated Islamic-Medicine skills. The results of this study can assist medical and health education providers in integrating Islamic content into their educational curriculum.